I believe the correct given equation is in the form:
f (x) = 2^x + 1 where
x is an exponent of the number 2
Now to solve for the average rate of change of the given
function from points x = 0 and x = 2, we must first assume that the graph
between those two points is linear. With that, we can solve for the average
rate of change using the slope formula, that is:
average rate of change = slope = [f (x2) – f (x1)] / (x2 –
x1)
Therefore,
average rate of change = [(2^2 + 1) – (2^0 + 1)] / (2 – 0)
average rate of change = [5 – 2] / 2
average rate of change = 3 / 2
average rate of change = 1.5